Specification of haematopoietic stem cell fate via modulation of mitochondrial activity - Nicola Vannini (Nature Portfolio, 2016)
Haematopoietic stem cells rely on glycolysis for their energy demands but whether this affects their fate is unknown. Here, the authors show that forcing the cells to rely on glycolysis is important for self-renewal and that this involves a reduction in mitochondrial mass.